Solving Oscillating Problems Using Modifying Runge-Kutta Methods - Ghazal, Zainab Khaled; Hussain, Kasim Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
This paper develop conventional Runge-Kutta methods of order four and order five to solve ordinary differential equations with oscillating solutions. The new modified Runge-Kutta methods (MRK) contain the invalidation of phase lag, phase lagâ€™s derivatives, and ampliï¬cation error. Numerical tests from their outcomes show the robustness and competence of the new methods compared to the well-known Runge-Kutta methods in the scientiï¬c literature.